2020
DOI: 10.1002/smll.202004409
|View full text |Cite
|
Sign up to set email alerts
|

Air Stable Organic–Inorganic Perovskite Nanocrystals@Polymer Nanofibers and Waveguide Lasing

Abstract: Hybrid organic-inorganic perovskites have attracted wide attentions owing to their potent optoelectronic applications associated with their unique features of excitons such as long carrier lifetime and diffusion length. [1,2] Since the discovery of Organic-inorganic hybrid perovskites have been considered as promising gain materials for lasing. Despite previous reports of lasing from nanocrystals, thin films and single crystals, the stability of perovskite lasers has been a challenge for its practical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…From the view of lasing applications, the control of the shape of the host matrix in order to vary the shape from fibers to spheres meeting the resonance conditions for further observation of amplified spontaneous emission (ASE) and lasing is needed [20,21]. In recent work [22], it was shown that the fibers based on composites made with pNCs and polymers (polymethyl methacrylate and poly(vinylidene fluoride)) had stable optical responses at humidity at 60% and performed ASE and waveguide lasing. He et al presented the fabrication of SiN nanoscale cavity covered by pNCs mixed with PMMA which showed lasing with Q-factor of 1.5 × 10 4 and threshold at 5.62 µJ/cm 2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…From the view of lasing applications, the control of the shape of the host matrix in order to vary the shape from fibers to spheres meeting the resonance conditions for further observation of amplified spontaneous emission (ASE) and lasing is needed [20,21]. In recent work [22], it was shown that the fibers based on composites made with pNCs and polymers (polymethyl methacrylate and poly(vinylidene fluoride)) had stable optical responses at humidity at 60% and performed ASE and waveguide lasing. He et al presented the fabrication of SiN nanoscale cavity covered by pNCs mixed with PMMA which showed lasing with Q-factor of 1.5 × 10 4 and threshold at 5.62 µJ/cm 2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…[128,229] Electrospinning is another scalable strategy to massively fabricate the polymer microfibers. [230] Based on this facile approach, Zhang et al prepared plasmonic enhanced polymer microfibers and demonstrated its ultrahigh sensitivity to the relative humidity and scetic acid gas. Thanks to the excellent fabric compatibility, the microfibers can be woven into the clothes to fabricate a wearable sensor (Figure 14c).…”
Section: Disposable Testmentioning
confidence: 99%
“…Recently, extensive investigations have been concentrated on the realization of lasers on the plastic substrate due to their mechanical flexible characteristics suitable for the development of flexible optoelectronic systems. [1][2][3][4][5] For example, the deposition of ZnO nanoparticle embedded ZnO thin film on polycarbonate plastic substrate is proposed to realize flexible inorganic random lasers. [6] Organic lasers using solvent-free fluidic organic semiconductors as the gain medium, and highly flexible corrugated polymeric patterns and flexible polyurethane acrylate films as the resonator have also achieved mechanically single-mode tunable lasers.…”
Section: Introductionmentioning
confidence: 99%